2011
DOI: 10.1007/s12010-011-9411-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipids Containing Polyunsaturated Fatty Acids Synthesized by Zygomycetes Grown on Glycerol

Abstract: Several strains of Zygomycetes cultivated on glycerol produced mycelia rich in lipids containing higher amounts of neutral lipids (NL) than glycolipids plus sphingolipids and phospholipids (P), while biosynthesis of P in Mortierella ramanniana, Mucor sp., and Cunninghamella echinulata occurred though NL accumulation process was in progress. Polyunsaturated fatty acids (PUFA) concentration gradually decreased in all lipid fractions of M. ramanniana during growth. In contrast, in C. echinulata concentration of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 51 publications
9
62
3
1
Order By: Relevance
“…However, this event was observed only in some Zygomycetes; e.g., M. ramanniana. On the contrary, the biosynthesis of PUFAs in C. echinulata continued after the cessation of growth, suggesting that the synthesis of PUFAs in this species is not a strictly growth-associated process [30]. We have previously found that the AA synthesis in the M. alpina strains, LPM-301 and NRRL-A-10995, depended considerably on the nature of growth-limiting components; AA synthesis reached a peak under growth limitations by glycerol and gradually decreased with the transition in culture to nitrogen limitations [20].…”
Section: The Effect Of Phmentioning
confidence: 89%
See 2 more Smart Citations
“…However, this event was observed only in some Zygomycetes; e.g., M. ramanniana. On the contrary, the biosynthesis of PUFAs in C. echinulata continued after the cessation of growth, suggesting that the synthesis of PUFAs in this species is not a strictly growth-associated process [30]. We have previously found that the AA synthesis in the M. alpina strains, LPM-301 and NRRL-A-10995, depended considerably on the nature of growth-limiting components; AA synthesis reached a peak under growth limitations by glycerol and gradually decreased with the transition in culture to nitrogen limitations [20].…”
Section: The Effect Of Phmentioning
confidence: 89%
“…As seen from Table 5 [16,29,30]. The maximum energy yield of lipids was higher than the mass yield of lipids and reached 27% in the continuous culture of M. alpina NRRL-A-10995 at 28 • C ( Table 5).…”
Section: Parametersmentioning
confidence: 94%
See 1 more Smart Citation
“…Bellou et al (35) found that the use of glycerol by Mortierella ramanniana did not alter the amounts of biomass in comparison with other strains of Mortierella cultivated on multiple carbon sources. However, these fungi accumulated more interesting compounds (lipids) whose production was associated with primary metabolism during mycelial growth.…”
Section: Eff Ect Of the Culture Medium Composition On Carotenoid Prodmentioning
confidence: 99%
“…Saccharomyces cerevisiae is the most common organism used for the fermentation of hexose, while zygomycetes fungi can utilize a wider range of monosaccharides, including pentoses, and are of high performance for ethanol production from lignocellulosic materials (Sues et al, 2005). Furthermore, the biomass of these fungi are valuable products with various applications, due to the fact the it contains considerable amounts of glucosamine (GlcN) and essential fatty acids (Chatterjee et al, 2005;Bellou et al, 2012). Glucosamine, an amino monosaccharide, is a major component of the cell wall.…”
Section: Introductionmentioning
confidence: 99%